An analysis on computer games addiction of secondary school students and their loneliness conditions - Öncel, Mustafa; Tekin, Ahmet (İnönü Üniversitesi, 2015)
Today, computer games are played widely by individuals of almost all ages for purposes such as entertainment, learning and for at least to some extent unwinding from the exhaustion that house and work life causes. Games to improve both physical skills of children and their mental activities have been designed especially recently. These games are developed by business organizations for profit, but they can also be developed by the Ministry of National Education to enhance school success of students. Students, who spend so much time on computer games at home, school or places like internet cafes; encounter psychological problems such as physical and behavioral disorders, social phobia and school phobia due to uncontrolled and uninspected computer games playing process. These psychological problems cause loneliness in children by detracting them from social and learning environments. Secondary school students’ game addictions and their effect on loneliness was examined. The study group of the study consisted of grade five, six, seven and eight students studying in a secondary school in the central district of Bingöl. The study was conducted with the screening method, one of the quantitative research methods. The first data collection instrument was the scale developed by Horzum, Ayas and Çakır Balta (2008) to determine game addictions of students, and whose reliability and validity analyses were completed. The other data collection instrument was developed by Rusell, Pepelau and Cutrona (1980) and translated into Turkish by Demir (1989) to determine the loneliness levels of students. In addition; gender, a questionnaire consisting of demographical information such as grade, mothers’ educational status, fathers’ educational status, grade point average, income level of the family was used in the study. Descriptive analyses on frequency, percentage and average, and relational analyses such as t-test and ANOVA were carried and the items of the scale were interpreted. According to the study results, there are no significant differences between gender and game addiction, students with low game addiction levels have low loneliness levels, but there are significant relationships between daily duration spent on playing games, grade levels, place where the game is played and addiction levels.

Bilgisayar oyunları hemen her yaştaki bireylerce eğlenmek, öğrenmek, ev ve iş hayatının verdiği yorgunluğu kısmen de olsa giderebilmek gibi çeşitli amaçlarla günümüzde yaygın bir şekilde oynanmaktadır. Özellikle son yıllarda çocukların gerek fiziksel becerilerinin gerekse zihinsel aktivitelerinin gelişimleri için birçok oyun tasarlanmıştır. Bu oyunlar çeşitli ticari kuruluşlar tarafından kar amaçlı oluşturulduğu gibi, MEB tarafından da okullarda öğrencilerin ders içi başarılarını geliştirmek amacıyla da oluşturulmaktadır. Evde, okulda, internet evi gibi yerlerde bilgisayar oyunları ile çokça vakit geçiren öğrenciler; kontrolsüz, denetimsiz bir bilgisayar oyunu oynama süreci sonunda çeşitli fiziksel ve davranış bozuklukları, sosyal fobi, okul fobisi gibi çeşitli psikolojik sorunlara maruz kalmaktadırlar. Yaşanan bu psikolojik sorunlar çocukları yalnızlığa iterek sosyal çevreden, sosyal öğrenme ortamlarından uzaklaştırabilmektedir. Bu çalışmada ortaokul öğrencilerinin oyun bağımlılıkları ve yalnızlığa etkisi araştırılmıştır. Araştırmanın çalışma grubunu Bingöl il merkezinde bulunan bir ortaokulun beşinci, altıncı, yedinci ve sekizinci sınıfında eğitim gören öğrenciler oluşturmaktadır. Çalışma nicel araştırma yöntemlerinden tarama yöntemi kullanılarak yürütülmüştür. Veri toplama araçlarından ilki, öğrencilerin oyun bağımlılıklarının belirlenmesi için Horzum, Ayas ve Çakır Balta (2008) tarafından geliştirilen, geçerlik güvenirlik analizi yapılmış ölçektir. Diğer veri toplama aracı olan ve öğrencilerin yalnızlık düzeylerinin belirlenmesi amacıyla hazırlanan yalnızlık ölçeği ise Rusell, Pepelau ve Cutrona (1980) tarafından hazırlanmış ve Demir (1989) tarafından Türkçe’ ye çevrilmiş olan ölçektir. Bunlara ek olarak; cinsiyet, sınıf, annenin eğitim durumu, babanın eğitim durumu,  not ortalaması, aile gelir durumu gibi öğrencilerin demografik bilgilerinin yer aldığı anket kullanılmıştır. Frekans, yüzde, ortalama gibi betimsel analizler ve t-testi, anova gibi bazı ilişkisel analizler yapılarak uygulanan ölçekteki maddeler yorumlanmıştır. Araştırma sonunda cinsiyet ile oyun bağımlılığı arasında anlamlı bir fark bulunmadığı, oyun bağımlılık düzeyi yüksek olan çocuklarda yalnızlık duygusunun daha düşük olduğu, sınıf düzeyleri ile oyun bağımlılık düzeyleri arasında anlamlı farklar olduğu bulunmuştur
Ortaokul öğrencilerinin bilgisayar oyun bağımlılığı ve yalnızlık durumlarının incelenmesi